Time to Say Goodbye? The Impact of Environmental Regulation on Foreign Divestment - Haiou Mao; Holger Görg; Guopei Fang (Institute of Labor Economics (IZA), 2023)
We look at divestments by foreign firms – a topic that has received comparatively little attention in the literature – and investigate how changes in the regulatory environment in the host country may impact on such divestment decisions. We use the implementation of China's Two Control Zone (TCZ) policy as a "quasi-natural experiment", using detailed firm level combined with city level data for the empirical analysis. Our results show that the implementation of TCZ policy has led to higher probabilities of divestments by foreign firms in targeted TCZ cities and industries. The mechanism behind this seems to be a TCZ-induced increase in discharge fees and efforts to reduce SO2 emissions. Allowing for heterogeneity of effects, we find that the effect is particularly strong for firms from source countries with less stringent environmental regulation, and those using less advanced technology. We furthermore show that firms using intermediates from polluting industries also experience a higher probability of divestment.
Keywords: F23; Q58; 330; foreign divestment; environmental regulation; Two Control Zone Policy; China